ANALISIS KOMPARATIF TENTANG HUKUM TALAK TIGA ANTARA FIQH KLASIK DAN HUKUM POSITIF - Sulaiman M. Thalib (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2013)
Thalaq or divorce, from literally just been symbolizes disharmony andhatred, it was hated, the Prophet SAW said that divorce is forbidden by Allah.Though hated but divorce is halal, Islam opened the door to divorce. Outstrippingdivorce is a divorce three, one and two because divorce can refer (back) during thewife's still in that period. Divorce, as in the case of marriage, arranged in theliterature of Islamic law, including the source ie the Qur'an and the Sunnah of theProphet. In the study of jurisprudence from time to time also take the discussionsurrounding the divorce because divorce procedures not specified in detail in theQur'an and the Sunnah of the Prophet. While cases that occur are as varied andcomplex. Wedlock and divorce are also arranged in the legislation that was termedby positive law. The purpose of this study is to find out how divorce threeconditions according to classical jurisprudence and positive law in Indonesia. Themethod used in this study is the method of literature research (library research),which is studying the classical scriptures of the mu'tabar in four schools andlegislation on marriage and other resources related to do a comparison. The resultsshowed that there were some differences between the provisions of divorce threeclassic books of jurisprudence and positive law in Indonesia.